Refueling a Quiet Fire: Old Truthers and New Discontent in the Wake of Covid-19 - Gabriele Beccari; Matilde Giaccherini; Joanna Kopinska; Gabriele Rovigatti (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates the factors that contributed to the proliferation of online COVID skepticism on Twitter across Italian municipalities. We demonstrate that socio-demographic factors are likely to mitigate the emergence of skepticism, while populist political leanings were more likely to foster it. Furthermore, we find that the presence of pre-COVID anti-vax sentiment, represented by old "truthers" on Twitter, amplifies online COVID skepticism in local communities. Additionally, exploiting the spatial variation in economic restrictive policies with severe implications for suspended workers belonging to non-essential economic sectors, we find that COVID skepticism spreads more in municipalities significantly affected by this economic lockdown. Finally, the diffusion of COVID skepticism is positively associated with COVID vaccine hesitancy.
Keywords: I12; I18; J28; J60; C80; L82; 330; Twitter; scepticism; public health; media; vaccines; Covid-19